PATTERNS OF PSYCHOLOGICAL AND PEDAGOGICAL INTERACTION BETWEEN TEACHER AND PARENTS OF PUPILS - Slobodianyk, Natalia (PSYCHOLOGICAL JOURNAL, 2018)
The article analyzes the essence, structure and peculiarities of the psycho-pedagogical interaction between teacher and parents of pupils, reveals the peculiarities of productive and unproductive interaction between teacher and parents, determines the patterns, principles, psychological and pedagogical conditions of productive interaction between teacher and parents of pupils. The signs of productive interaction between teacher and parents of pupils are presented: communication, knowledge of the laws and the structure of pedagogical communication; recognition of the value of the family, interaction with the family, ability to reflect the interaction with the family, humanization of interpersonal relationships. It is concluded that psychological and pedagogical conditions of productive interaction between teacher and parents of pupils are logically interconnected and interdependent. The implementation of personal-active, dialogical, individual-creative approaches determines the strategy, determines the choice of tactics of teacher’s actions in the process of interaction with parents of pupils. It isnoted that in the process of psychological and pedagogical interaction between teacher, schoolchildren and parents there are various interconnected and interdependent relations and connections. It is determined that the content of the work of the pedagogical team with parents is to increase the psychological and pedagogical knowledge of the parents (lectures, seminars, individual consultations, workshops, conferences, parent training; parental rings); involvement of parents in the educational process (parent meetings, general creative affairs). Parent conferences are of great importance in the system of educational work of the school. During such conferences, it is possible to discuss topical problems of society, the reasons of conflicts between parents and children and waysof solving for such situations; gender issues and problems of sex education in family.It is concluded that the interaction between teachers and parents in an educational institution is an integral socio-psychological system, which combines the unity of perceptual (common consciousness), communicative (communication) and interactive (cooperation, co-creation) interrelated components.